Islamist political activism and education volunteerism :|a local ulema movement in the late Ottoman Konya, 1909-1921 - Taşkın, Süleyman. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This thesis focuses on a certain conservative group from ulema and Nakshi Khalidi sufis led by a particular Sheikh family in the Late Ottoman city of Konya. It tries to explain how could a traditional Sufi order turn to be a modern socio-political movement and became engaged with politics and reforming formal education at its madrasa by using modern devices. Understanding their theological perspective and looking at their anxieties over what they interpreted as innovation and secularization were keys to comprehend the story of the movement. To locate them in the general framework of the late Ottoman history, the thesis touches upon the discussions related to the Islamic modernism, and historiography over the late Ottoman ulema, which was often regarded as distinct areas of research. Therefore, this thesis deals with the the constitutional period experiences of the various late Ottoman ulema and Islamic intellectuals as much as it focused on their reflections in the local context of Konya. The city could be the most suitable place after the capital for tracing and observing the mentality and concrete applications of the opposing Muslim stances about reform and tradition on the ground. What this specific group in Konya experienced is a story of opposition and marginalization, except for small opportunities for power. By relying on a more conservative outlook, the group carried out a continuous opposition against the official Islam of the power holders in the late Ottoman period, respectively of the Hamidian regime, the CUP and its successor National Movement in Ankara.
Keywords: Ulama -- Political activity -- Turkey -- Konya.; Islam and politics -- Turkey.